2008
DOI: 10.1001/archpsyc.65.7.762
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-up of a Randomized Multicenter Trial of Intensive Early Intervention vs Standard Treatment for Patients With a First Episode of Psychotic Illness

Abstract: The intensive early-intervention program improved clinical outcome after 2 years, but the effects were not sustainable up to 5 years later. Secondary outcome measures showed differences in the proportion of patients living in supported housing and days in hospital at the 5-year follow-up in favor of the intensive early-intervention program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
433
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 417 publications
(454 citation statements)
references
References 36 publications
18
433
2
1
Order By: Relevance
“…For the trials with long term follow-up after the end of the intervention period, the results were more contradictory 1415 16 The largest randomised clinical trial of SEI treatment, the OPUS I trial,3 15 17 found that participants in the intervention group relapsed to the psychopathological and functional levels of the control participants three years after the end of the intervention 15. In a naturalistic study from Canada, researchers testing the effect of five years of SEI treatment found that they could sustain and further reduce the psychopathology and increase the functional level of the participants 18…”
Section: Introductionmentioning
confidence: 99%
“…For the trials with long term follow-up after the end of the intervention period, the results were more contradictory 1415 16 The largest randomised clinical trial of SEI treatment, the OPUS I trial,3 15 17 found that participants in the intervention group relapsed to the psychopathological and functional levels of the control participants three years after the end of the intervention 15. In a naturalistic study from Canada, researchers testing the effect of five years of SEI treatment found that they could sustain and further reduce the psychopathology and increase the functional level of the participants 18…”
Section: Introductionmentioning
confidence: 99%
“…The research, development and implementation of early intervention (EI) services in psychotic disorders over the past nearly two decades are now well established and the benefits well documented [3][4][5][6][7]. This has been achieved through a major philosophical shift in the conceptual framework of the disorder and changes in the form and content of services modified to meet the needs of younger and treatment naïve patients.…”
Section: Early Intervention In Psychosis and Youth Mental Health Servmentioning
confidence: 99%
“…In particular, an increasing body of evidence suggests that treatment of patients with schizophrenia may be more effective when initiated and maintained early in the course of the disease 3, 4, 5, 6. Evidence suggests that treatment response tends to diminish with each successive psychotic episode and that most functional deterioration occurs within 5 years of onset 1, 7.…”
Section: Introductionmentioning
confidence: 99%